Pengaruh Kompetensi Kerja dan Motivasi Kerja Terhadap Kinerja Pegawai Melalui Komitmen Organisasi Sebagai Variabel Intervening pada Rumah Sakit Islam Jakarta Cempaka Putih - Faikhotul Inayah; Maswanto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The purpose of this study was to examine the influence of Job Competence and Work Motivation on Employee Performance through Organizational Commitment as an Intervening Variable at the Jakarta Islamic Hospital, Cempaka Putih. This study was quantitative and associative in nature, with non-medical employees of the Jakarta Islamic Hospital, Cempaka Putih, as the respondents. This study was a population study with 180 respondents. The data processing tool used was the Partial Least Squares Structural Equation Modeling (PLS-SEM) method using the SmartPLS version 4.0 application, which aims to analyze the relationship between latent constructs and path models. This can be seen through the results of the outer model, or measurement model, and the inner model, or structural model. The partial results of this study are: 1) Job Competence significantly influences Organizational Commitment. 2) Work Motivation significantly influences Organizational Commitment. 3) Work Competence significantly influences Employee Performance. 4) Work Motivation does not significantly influence Employee Performance. 5) Organizational Commitment significantly influences Employee Performance. 6) Work Competence significantly influences Employee Performance through Organizational Commitment as an Intervening Variable. 7) Work Motivation significantly influences Employee Performance through Organizational Commitment as an Intervening Variable.